Angiotensin-(1-7) attenuated long-term hypoxia-stimulated cardiomyocyte apoptosis by inhibiting HIF-1α nuclear translocation via Mas receptor regulation. (2nd January 2016) - Chang, Ruey-Lin; Lin, Jing-Wei; Kuo, Wei-Wen; Hsieh, Dennis Jine-Yuan; Yeh, Yu-Lan; Shen, Chia-Yao; Day, Cecilia-Hsuan; Ho, Tsung-Jung; Viswanadha, Vijaya Padma; Huang, Chih-Yang
Abstract: Extreme hypoxia often leads to myocardial apoptosis and causes heart failure. Angiotensin-(1-7)Ang-(1-7) is well known for its cardio-protective effects. However, the effects of Ang-(1-7) on long-term hypoxia (LTH)-induced apoptosis remain unknown. In this study, we found that Ang-(1-7) reduced myocardial apoptosis caused by hypoxia through the Mas receptor. Activation of the Ang-(1-7)/Mas axis down-regulated the hypoxia pro-apoptotic signaling cascade by decreasing the protein levels of hypoxia-inducible factor 1α (HIF-1α) and insulin-like growth factor binding protein-3 (IGFBP3). Moreover, the Ang-(1-7)/Mas axis further inhibited HIF-1α nuclear translocation. On the other hand, Ang-(1-7) activated the IGF1R/PI3K/Akt signaling pathways, which mediate cell survival. However, the above effects were abolished by A779 treatment or silencing of Mas expression. Taken together, our findings indicate that the Ang-(1-7)/Mas axis protects cardiomyocytes from LTH-stimulated apoptosis. The protective effect of Ang-(1-7) is associated with the inhibition of HIF-1α nuclear translocation and the induction of IGF1R and Akt phosphorylation.